A database of functional traits for spiders from native forests of the Iberian Peninsula and Macaronesia - Macías-Hernández, Nuria (Biodivers Data J, 2020)
BACKGROUND: There is an increasing demand for databases including species trait information for biodiversity and community ecology studies. The existence of trait databases is useful for comparative studies within taxa or geographical regions, but there is low availability of databases for certain organisms. Here we present an open access functional trait database for spiders from Macaronesia and the Iberian Peninsula, recording several morphological and ecological traits related to the species life histories, microhabitat and trophic preferences. NEW INFORMATION: We present a database that includes 12 biological traits for 506 spider species present in natural forests of the Iberian Peninsula (Spain) and three Macaronesian archipelagoes (Azores, Madeira and Canary Islands). The functional trait database consists of two sections: 1. individual-level data for six morphological traits (total body size, prosoma length, prosoma width, prosoma height, tibia I length and fang length), based on direct measurements of 2844 specimens of all spider species; and 2. species-level aggregate data for 12 traits (same 6 morphological traits as in the previous section plus dispersal ability, vertical stratification, circadian activity, foraging strategy, trophic specialization and colonization status), based on either the average of the direct measurements or bibliographic searches. This functional trait database will serve as a data standard for currently ongoing analyses that require trait and functional diversity statistics.